A biomechanical comparison of countermovement performance after short-term traditional and daily-undulated loaded vertical jump training. Issue 16 (18th August 2018) - Pelzer, Thiemo; Ullrich, Boris; Endler, Stefan; Rasche, Christian; Pfeiffer, Mark
ABSTRACT: In order to assess lower extremity muscle mechanical properties in athletes, power-load characteristics during multi-joint tasks are frequently examined. This work compared 6 weeks of traditional (TP) and daily-undulated (DUP) periodized loaded countermovement jumping (CMJ). 20 amateur athletes (age: 24.2 ± 2.6 years, height: 175.6 ± 7.1 cm, body mass: 71.5 ± 7.7 kg, 10 males/10 females) exercised three times weekly using maximal CMJs with loads corresponding to 0%, 15% and 30% of body mass. Prior to the training period, subjects were once-only assigned by random to either the TP or DUP training scheme. Pre-to-post training, maximal center of mass (COM) -height, -take-off velocity, -power output and -impulse were compared during CMJ with additional loads corresponding to 0–30% of body mass. ANOVA (time * group) with repeated measures revealed significant ( P  < 0.05) temporal gains of maximal COM-height (2–11%), -take-off velocity (1–7%), -power (2–8%) and -impulse (3–9%) over most loading conditions for TP and DUP. However, ANOVA indicated no group effects for any outcome. Independent from the periodization model, maximal power output remained statistically unchanged with increased testing loads. For short-term conditioning periods, TP and DUP were equally effective in enhancing biomechanical jumping variables under varying loading conditions.